APLIKASI PENGGAJIAN BERBASIS WEB MENGGUNAKAN PHP PADA PT ANUGERAH MOTOR KANDANGAN - Muhammad Luthfi Akbar; Ahsanul Haq; M.Hendra Sunarya; Priyougie (Jurnal Riset Multidisiplin Edukasi, 2025)
The author of this study chooses to focus on payroll. In order to complete the final project requirement, PT Anugerah Motor Kandangan is the subject of the research study. The present payroll calculation method, which still depends on printed attendance data, manual computations, and subsequent compilation into Excel, is the reason behind the background of this study. The objective of this study is to create a system that expedites the payroll computation procedure and the gathering of employee attendance data. A case study methodology is employed in the research, incorporating direct documentation at the research location and interviews. Both qualitative and quantitative data kinds are employed. The results of this research include discussing information systems, developing a payroll application program that meets the needs of the subject, introducing innovations in the application, and providing several recommendations for the subject.